Energetics of different in-situ moisture conservation practices in maize (Zea mays) - Jat, M L; Singh, P; Balyan, J K; Gupta, A; Jain, L K (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during rainy season (kharif) 2000-2003 at Dryland Research Farming Station, Arjia, Bhilwara. Rajasthan, on different in-situ moisture conservation practices for raising maize (Zea mays L.). Six in situ moisture conversation practices were tried for raising maize. The highest grain yield (1.53 tonnes/ha) and energy ratio (14.65) was observed in flat sowing and ridging after first intercultural operation. The fertilizer accounted maximum share of energy (nearly 50 %) in dryland areas.